Irrigation schedule for maximum corm yield and water productivity in elephant foot yam (Amorphophallus paeoniifolius) - SUNITHA, S; GEORGE, JAMES; SUJA, G; RAVI, V; HARIPRIYA, S; SREEKUMAR, J (The Indian Journal of Agricultural Sciences, 2018)
Field experiments were carried out on elephant foot yam [Amorphophallus paeoniifolius (Dennst.) Nicolson] during 2013-2014 and 2014-2015 to study the effect of different irrigation schedules in order to arrive at an optimum schedule for attaining maximum corm yield and water productivity. Two methods (Drip and Flood methods ) and two levels of irrigation (75% and 100% pan evaporation) were applied at different stages of growth as first 12 weeks, 13-24 weeks, 1-24 weeks, 75% during first 12 weeks and 100% during 13-24 weeks after planting and vice versa. Whole corm size of 500 g each of the variety ’Gajendra’ was uniformly used as the planting material. Pooled analysis of the data showed superiority of drip irrigation over flood irrigation. Among the treatment combinations, drip irrigation at 100% pan evaporation during 13-24 weeks after planting resulted in the maximum corm yield (40.59 t/ha). However, this was at par with drip or flood irrigation given during the entire period of 1-24 weeks at 75% and 100% levels. Drip irrigation at 100% pan evaporation during 13-24 weeks resulted in maximum water productivity (4.57 kg/m3). Under flood irrigation, maximum water productivity recorded was 3.87 kg/m3. Irrigation during 13-24 weeks after planting coinciding with corm development stage was found to be more critical than irrigation given during the initial stages of planting. The study revealed that drip irrigation at 100% pan evaporation during 13-24 weeks after planting is the most ideal for attaining maximum corm yield and water productivity in elephant foot yam.